Determining for the Interaction of Constitutive Androstane Receptor and CITCO Using a Surface Plasmon Resonance Based Biosensor System - Dau, Pham Thi; Ha, Le Thu; Tuyen, Le Huy; Huong, Pham Thi Thu; Iwata, Hisato (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: This study investigated the binding affinity of constitutive androstane receptor (CAR) with its activator, 6-(4-chlorophenyl)imidazo[2,1-b][1,3]thiazole-5-carbaldehyde O-(3,4-dichlorobenzyl) oxime (CITCO) in order to develop a rapid method for screening of protein-binding compounds. At first, the performance capacity of surface plasmon resonance (SPR) system was confirmed by the interaction of commercial carbonic anhydrate II (CAII) protein and 4-carboxybenzenesulfonamide (CBS) compound. The target protein, ligand binding domain of human CAR (hCAR), was optimally immobilized on SPR sensor chip using amine coupling method and then used to detect the interaction with chemical molecules. CITCO, known as a hCAR agonist in previous studies was used as the positive control to develop the method for determination of the binding affinities between SPR-immobilized CAR proteins and chemicals. As expected, CITCO showed specific bindings to hCAR protein in this study, indicating the application potential of SPR system in screening probable ligands of proteins. Keywords: Constitutive androstane receptor, CITCO, surface plasmon resonance.